A novel, dual acting, soft pellet formulation, combining cushioning and rapid disintegration properties, and their incorporation into tablet formulations containing film-coated drug pellets. (8th November 2010) - Pick-Katolik, Jan; Podczeck, Fridrun
This work reports the concept of a novel, dual-acting, 'soft' pellet formulation, which protects film-coated 'hard' pellets during tabletting. The novel 'soft' pellets were designed to both cushion film-coated pellets during tabletting and ensure rapid disintegration of the tablets when in contact with water. The deformability and disintegration properties of these pellets were controlled using olive oil. 'Hard' pellets, produced by extrusion/spheronisation, were optimised and characterised and were film coated with Kollicoat® SR30D, containing triethyl citrate as plasticiser and fluorescein sodium as marker substance. Several coating thicknesses and plasticiser concentrations were studied using a statistically designed experiment. 'Soft' pellets produced using extrusion/spheronisation or granulation/spheronisation, were tabletted with either film-coated ibuprofen pellets or theophylline pellets and their dissolution and disintegration properties were determined. Granulation/spheronisation was the preferred method of manufacture of the soft pellets and lower percentages of olive oil were found to be more beneficial to the disintegration properties of the compacts.